STRATEGI PROMOSI MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PENGGUNA JASA KATIRA MAKE UP ARTIST & HAIRDO DI SERANG: STRATEGI PROMOSI MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PENGGUNA JASA KATIRA MAKE UP ARTIST & HAIRDO DI SERANG (Faletehan Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted to determine the type of promotion strategy through Instagramsocial media on the decisions of KATIRA MAKEUP & HAIRDO service users in Serang. Thistype of research is explanatory, with data collection techniques through questionnaires. Thesampling technique used was simple random sampling technique. The sample is 30 people whoare followers on Instagram and consumers of each make-up artist (MUA). The analyticalmethod used in this study is Quantitative Analysis. The results of the study can be seen that the tvalue of the promotional strategy variable is 10.301 and the t table is 1.984. Because the valueof t count 10.301 > t table 1,984, it can be concluded that H1 is accepted. This means that thepromotion strategy variable has a significant positive effect on the Purchase Decision variable